2019
DOI: 10.1007/978-3-030-29390-1_14
|View full text |Cite
|
Sign up to set email alerts
|

What Is Beautiful Continues to Be Good

Abstract: Image recognition algorithms that automatically tag or moderate content are crucial in many applications but are increasingly opaque. Given transparency concerns, we focus on understanding how algorithms tag people images and their inferences on attractiveness. Theoretically, attractiveness has an evolutionary basis, guiding mating behaviors, although it also drives social behaviors. We test image-tagging APIs as to whether they encode biases surrounding attractiveness. We use the Chicago Face Database, contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In the HCI literature, auditing often involves characterizing the behavior of the algorithm from a user perspective. For instance, in Matsangidou and Otterbacher [94], the authors consider the inferences on physical attractiveness made by image tagging algorithms on images of people. They audited the output of four image recognition APIs on standardized portraits of people across genders and races.…”
Section: Auditing Approaches For Bias Detectionmentioning
confidence: 99%
“…In the HCI literature, auditing often involves characterizing the behavior of the algorithm from a user perspective. For instance, in Matsangidou and Otterbacher [94], the authors consider the inferences on physical attractiveness made by image tagging algorithms on images of people. They audited the output of four image recognition APIs on standardized portraits of people across genders and races.…”
Section: Auditing Approaches For Bias Detectionmentioning
confidence: 99%
“…These characteristics can have an influence on how people are perceived by others. For instance, it is well documented in studies, such as that of Matsangidou and Otterbacher [13], that those who are perceived to be more attractive are assumed to possess more desirable personality traits and tend to be more successful occupationally. One very early study conducted by Steffensmeier et al [14] found that individuals who were dressed in "hippy"-style clothing were significantly more likely to be reported by other customers for shoplifting than those who were wearing "straight" clothing such as a suit and tie.…”
Section: Physical Appearancementioning
confidence: 99%